“I Smile Too When I Think of You”: The Beginning of the Friendship between Bronė Jacevičiūtė-Jėčiūtė and Janina Degutytė. Intermedial Source and Initial Research of the Relationship - Šmitienė, Giedrė (Colloquia, 2024)
-